Penegakan Hukum Terhadap Pemasangan Reklame Tidak Sah di Kota Pangkalpinang Berdasarkan Peraturan Daerah Kota Pangkalpinang Nomor 16 Tahun 2012 tentang Penyelenggaraan Reklame - HTPA, Anggriyani; Agustian, Rio Armanda; Toni, Toni (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
Law enforcement is the entire process and efforts carried out by authorized officers or institutions to ensure that applicable laws are truly obeyed and implemented fairly, consistently, and firmly. The act of installing unauthorized advertisements that violate the laws and regulations in force in a region can be said to be a criminal act, because it can be qualified as an unlawful act that results in material losses for the local government, endangers public safety, and damages the aesthetics of the city, and is carried out by individuals or business entities. This study aims to determine how law enforcement is carried out against the installation of unauthorized advertisements in Pangkalpinang City based on Pangkalpinang City Regional Regulation Number 16 of 2012 concerning Advertising Implementation and to determine what inhibiting factors are faced in law enforcement against the installation of unauthorized advertisements in Pangkalpinang City. The type of research used by the author in this study is Juridical-Empirical research, with the Legal Identification approach method. The results of the research that has been carried out, the enforcement efforts carried out are preventive efforts such as issuing warning letters and sealing and repressive efforts in the form of dismantling illegal advertisements which are considered less effective in providing a deterrent effect for perpetrators of installing illegal advertisements, considering that the number of illegal advertisements that are installed does not differ much each month and in the regulation itself there are other repressive efforts such as imprisonment and fines.